Determination of Trace Zearalenone and Its Metabolites in Human Serum by a High-Throughput UPLC-MS/MS Analysis - Danlei Sun; Chenglong Li; Shuang Zhou; Yunfeng Zhao; Yun Yun Gong; Zhiyong Gong; Yongning Wu (Applied Sciences, 2019)
This paper described an improved method for high-throughput and sensitive determination of zearalenone and its five metabolites (zearalanone, α-zearalenol, β-zearalenol, α-zearalanol and β-zearalanol) in human serum. Serum samples were measured both before and after enzyme hydrolysis to assess the free and total amount of each compound by ultra-performance liquid chromatography⁻tandem mass spectrometry (UPLC-MS/MS) in multi reaction monitoring (MRM) mode following off-line 96-well μElution solid-phase extraction (SPE). All the analytes were completely separated on a C18 column within 6 min. It enabled multi-sample preparation at the same time eliminating tedious evaporation and reconstitution steps, allowing 96 (one plate) samples to be processed and analyzed within 24 h. Using an isotope labelled internal standard (13C-ZEN), high recoveries were achieved for all the compounds in the range 91.6%⁻119.5%, with intra-day and inter-day relative standard deviations (RSDs) of less than 8%. The limits of detection (LOD) and the limits of quantification (LOQ) were 0.02⁻0.06 ng mL−1 (0.6⁻2 fmol) and 0.1⁻0.2 ng mL−1 (3⁻6 fmol), respectively, demonstrating a notable enhancement in sensitivity compared to the existing methods. The validated method was applied to the analysis of paired urine and serum samples collected from 125 healthy individuals in Henan Province, locating in the middle area of China. ZEN metabolites in human serum were significantly lower than those in urine. Only one serum sample was positive for ZEN after enzyme digestion, whereas at least one of ZEN biomarkers was detected in 75.2% of the paired urine samples. Some comparison and discussion were also included in this paper.